Syntactic and pragmatic features: a case study - D’Alessandro, Roberta (Revista Leitura, 2019)
In the generative literature, it has always been assumed that syntactic agreement takes place by means of syntactic operations that target the so-called phi-features. Lexical items are not atomic, but rather made up of phonetic material plus syntactic features, which encode grammatical information regarding, for example, number, gender, person, and case. According to Chomsky’s Derivation by Phase, syntactic agreement happens between two lexical items when two operations take place: Merge and Agree. If both these operations occur, syntactic agreement is established. In this paper, I shall move some objections against the traditional idea of phi-features and agreement. These objections derive directly from data observation. I shall show that some agreement and interpretational patterns of Italian impersonal si an European Portuguese a gente constructions are unexplainable within the current generative theory. I shall therefore argue for the existence of an additional set of features encoding pragmatic/deictic feature set, which I call the sigma-set (see D’Alessandro, 2004), is responsible for the so-called semantic agreement phenomena that have often been considered as solely acting in the pragmatic component of the grammar (Wechsler and Zlatió, 2001). I propose instead that pragmatic information is encoded syntactically, in the sigma-set, which appears a least in personal pronouns. DOI: 10.28998/0103-6858.2004v1n33p185-202